From political Islam to democrat Muslim: A comparison between Rashid Ghannouchi and Anwar Ibrahim - Malik, Maszlee; Mohamad Shukri, Syaza Farhana (International Islamic University Malaysia., 2018)
The relationship between Islam with a democratic political system has been questionable at best and incompatible at worst. While countless research has been done on this issue for decades especially with the rise of Islamist apologists in the years following the invasion of Iraq in 2003, this paper proposes that it is time we understand the role of Islam through the lenses of democrat Muslims. Democrat Muslims are those who seek to preserve and promote the five major qualities in human life with values that surpass simply protecting the people’s political, social and economic life. By comparing Rashid al-Ghannouchi and Anwar Ibrahim, this paper traces their evolution to come to a similar conclusion that is applicable to most Muslim societies. Using the dissonant politics theory, this paper suggests that local developments were taken into high consideration when these two figures decided to conceptualize what is known today as Democrat Muslims.